Development of a multiplex qRT-PCR assay for the detection of porcine epidemic diarrhea virus, porcine transmissible gastroenteritis virus and porcine Deltacoronavirus - Li, Yan; Niu, Jia-Wei; Zhou, Xia; Chu, Pin-Pin; Zhang, Kun-Li; Gou, Hong-Chao; Yang, Dong-Xia; Zhang, Jian-Feng; Li, Chun-Ling; Liao, Ming; Zhai, Shao-Lun (Frontiers in Veterinary Science, 2023)
Currently, porcine coronaviruses are prevalent in pigs, and due to the outbreak of COVID-19, porcine coronaviruses have become a research hotspot. Porcine epidemic diarrhea virus (PEDV), Transmissible Gastroenteritis Virus (TGEV), and Porcine deltacoronavirus (PDCoV) mentioned in this study mainly cause diarrhea in pigs. These viruses cause significant economic losses and pose a potential public health threat. In this study, specific primers and probes were designed according to the M gene of PEDV, the S gene of TGEV, and the M gene of PDCoV, respectively, and TaqMan probe-based multiplex real-time quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was developed for the simultaneous detection of PEDV, TGEV, and PDCoV. This method has high sensitivity and specificity, and the detection limit of each virus can reach 2.95 × 100 copies/μl. An assay of 160 clinical samples from pigs with diarrhea showed that the positive rates of PEDV, TGEV, and PDCoV were 38.13%, 1.88%, and 5.00%; the coinfection rates of PEDV+TGEV, PEDV+PDCoV, TGEV+PDCoV, PEDV+TGEV+PDCoV were 1.25%, 1.25%, 0%, 0.63%, respectively. The positive coincidence rates of the multiplex qRT-PCR and single-reaction qRT-PCR were 100%. This method is of great significance for clinical monitoring of the porcine enteric diarrhea virus and helps reduce the loss of the breeding industry and control the spread of the disease.